2007
DOI: 10.1021/bi700256z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Structural Analysis of Human Spermidine/Spermine N1-Acetyltransferase,

Abstract: The N1-acetylation of spermidine and spermine by spermidine/spermine acetyltransferase (SSAT) is a crucial step in the regulation of the cellular polyamine levels in eukaryotic cells. Altered polyamine levels are associated with a variety of cancers as well as other diseases, and key enzymes in the polyamine pathway, including SSAT, are being explored as potential therapeutic drug targets. We have expressed and purified human SSAT in Escherichia coli and characterized its kinetic and chemical mechanism. Initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
54
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 37 publications
7
54
1
Order By: Relevance
“…The acetylation rate of N 1 AcTETA was approximately 10% at 10 mM compared with TETA at 10 mM using the spectrophotometric method (Coleman et al, 2004) (data not shown). Furthermore, we determined the kinetic values for acetylation of TETA using hSSAT1 to compare the properties of the human and mouse recombinant enzymes that show high structural homology (Hegde et al, 2007;Montemayor and Hoffman, 2008 (Weisell et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The acetylation rate of N 1 AcTETA was approximately 10% at 10 mM compared with TETA at 10 mM using the spectrophotometric method (Coleman et al, 2004) (data not shown). Furthermore, we determined the kinetic values for acetylation of TETA using hSSAT1 to compare the properties of the human and mouse recombinant enzymes that show high structural homology (Hegde et al, 2007;Montemayor and Hoffman, 2008 (Weisell et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we propose the reaction mechanism (Fig. 2e), which resembles the described catalytic mechanism for lysine acetyltransferases (19).…”
Section: Resultsmentioning
confidence: 54%
“…In mammalian cells, polyamine acetylation is the first ratelimiting step in polyamine catabolism, and the human acetyltransferase, spermidine/spermine N 1 -acetyltransferase, is highly regulated due to the association of polyamine abundance with cellular proliferation (19,20,28). Through our newly determined crystal structure of vPAT and characterization of its catalytic activity as a polyamine acetyltransferase, we describe for the first time a virally encoded polyamine acetyltransferase with a catalytic efficiency (K m ϭ 21 M and k cat ϭ 131 min…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3]. Recent research showed that the polyamine derivatives based on spermidine and spermine exhibit high activity against Alzheimer's disease, cystic fi brosis, and also of various tumors and cancer cells [4][5][6][7]. 1,3-Propylenediamine fragment are included into the structure of many drugs used in the treatment of the central nervous system [e.g., antidepressant imipramine (tofranil)] [3].…”
mentioning
confidence: 99%